Changes in Lifestyle and Risk of Colorectal Cancer in the European Prospective Investigation Into Cancer and Nutrition. (12th April 2023) - Botteri, Edoardo; Peveri, Giulia; Berstad, Paula; Bagnardi, Vincenzo; Chen, Sairah L.F.; Sandanger, Torkjel M.; Hoff, Geir; Dahm, Christina C.; Antoniussen, Christian S.; Tjønneland, Anne; Eriksen, Anne Kirstine; Skeie, Guri; et al.
Abstract : INTRODUCTION: We investigated the impact of changes in lifestyle habits on colorectal cancer (CRC) risk in a multicountry European cohort. METHODS: We used baseline and follow-up questionnaire data from the European Prospective Investigation into Cancer cohort to assess changes in lifestyle habits and their associations with CRC development. We calculated a healthy lifestyle index (HLI) score based on smoking status, alcohol consumption, body mass index, and physical activity collected at the 2 time points. HLI ranged from 0 (most unfavorable) to 16 (most favorable). We estimated the association between HLI changes and CRC risk using Cox regression models and reported hazard ratios (HR) with 95% confidence intervals (CI). RESULTS: Among 295, 865 participants, 2, 799 CRC cases were observed over a median of 7.8 years. The median time between questionnaires was 5.7 years. Each unit increase in HLI from the baseline to the follow-up assessment was associated with a statistically significant 3% lower CRC risk. Among participants in the top tertile at baseline (HLI > 11), those in the bottom tertile at follow-up (HLI ≤ 9) had a higher CRC risk (HR 1.34; 95% CI 1.02–1.75) than those remaining in the top tertile. Among individuals in the bottom tertile at baseline, those in the top tertile at follow-up had a lower risk (HR 0.77; 95% CI 0.59–1.00) than those remaining in the bottom tertile. DISCUSSION: Improving adherence to a healthy lifestyle was inversely associated with CRC risk, while worsening adherence was positively associated with CRC risk. These results justify and support recommendations for healthy lifestyle changes and healthy lifestyle maintenance for CRC prevention.